Antiplaque effect of essential oils and 0.2% chlorhexidine on an in situ model of oral biofilm growth: a randomised clinical trial. - Víctor Quintas; Isabel Prada-López; Nikolaos Donos; David Suárez-Quintanilla; Inmaculada Tomás (PLoS ONE, 2015)
OBJECTIVE:To evaluate the in situ antiplaque effect after 4 days of using of 2 commercial antimicrobial agents in short term on undisturbed plaque-like biofilm. TRIAL DESIGN AND PARTICIPANTS:An observer-masked, crossover randomised clinical trial on 15 oral and systemically healthy volunteers between 20-30 years who were randomly and sequentially allocated in the same group which performed 3 interventions in different randomised sequences. INTERVENTION:The participants wore an appliance in 3 different rinsing periods doing mouthwashes twice a day (1/0/1) with essential oils, 0.2% chlorhexidine or sterile water (negative control). At the end of each 4-day mouthwash period, samples were removed from the appliance. Posteriorly, after bacterial vital staining, samples were analysed using a Confocal Laser Scanning Microscope. MAIN OUTCOME MEASURES:Bacterial vitality, thickness and covering grade by the biofilm after 4 days of applying each of the mouthwashes. RESULTS:The essential oils and the 0.2% chlorhexidine were significantly more effective than the sterile water at reducing bacterial vitality, thickness and covering grade by the biofilm. No significant differences were found between the 0.2% chlorhexidine and the essential oils at reducing the bacterial vitality (13.2% vs. 14.7%). However, the 0.2% chlorhexidine showed more reduction than the essential oils in thickness (6.5 μm vs. 10.0 μm; p<0.05) and covering grade by the biofilm (20.0% vs. 54.3%; p<0.001). CONCLUSION:The essential oils and 0.2% chlorhexidine showed a high antiplaque effect. Although the 0.2% chlorhexidine showed better results with regard to reducing the thickness and covering grade by the biofilm, both antiseptics showed a high and similar antibacterial activity. CLINICAL RELEVANCE:Daily essential oils or 0.2% chlorhexidine mouthwashes are effective when reducing dental plaque formation in the short term. Although 0.2% chlorhexidine continues to be the "gold standard" in terms of antiplaque effect, essential oils could be considered a reliable alternative. TRIAL REGISTRATION:ClinicalTrials.gov NCT02124655.